2018
DOI: 10.17660/actahortic.2018.1217.42
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis in the selection of groups of peach cultivars

Abstract: Brazil ranks 14 th in the world in terms of peach and nectarine production. Of the nearly 211,000 tons total output, the state of Rio Grande do Sul produces 60% of the national production, while southern Brazil accounts for 75%. This indicates that adequate parameters are required to manage the nutritional status of all fruit trees, of which the peach tree is an important component, as well as the performance of long-term experiments under field conditions in several, but often restricted, numbers of cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Research has shown the importance of phenological stage grouping for modeling [6,10,98]. Moreover, advances in fruit tree fertilizing indicate different nutrition profiles for each cultivar [12,99,100] or site-specific conditions [101] and, while requiring further elucidation, have the potential to leverage soil data predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown the importance of phenological stage grouping for modeling [6,10,98]. Moreover, advances in fruit tree fertilizing indicate different nutrition profiles for each cultivar [12,99,100] or site-specific conditions [101] and, while requiring further elucidation, have the potential to leverage soil data predictive power.…”
Section: Discussionmentioning
confidence: 99%
“…Peach cultivars surveyed in Southern Brazil showed differential nutritional profiles, and it may lead to cultivar-specific fertilization [65]. 'Esmeralda' nutrient ranges (Table 4) were narrow and differed from nutrient standards suggested for Southern Brazil [37], or elaborated among peach cultivars surveyed in Rio Grande do Sul State, Brazil [39].…”
Section: Foliar Nutrientsmentioning
confidence: 99%
“…Parent and Dafir [23] developed the compositional nutrient diagnosis in plants using row-centered log-ratios (clr). Thereafter, compositional data transformation has been used to preprocess combined nutrients traits of plant species and cultivars [13,[24][25][26] as well as animal species [27], and human food [28,29].…”
Section: Introductionmentioning
confidence: 99%